NEW MODEL OF ATOM (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In this research paper I have proposed a new model of the atom. Though it sounds, atomic physics is a closed research area since a century ago. But I have discovered some problems in the existing model of atom. In this model, I have proposed a static model of the atom, instead of the existing model which is based on matter waves. Here the electrons are not moving, or rotating, and so no s, p, d, f, sub shells for the atom, without which I have explained, the chemical and radiation nature of the atom.